A study of the marine cargo underwriting and claims in Singapore - Chai, Richard (2013)
This study aims to give the readers an insight into the operations of the marine cargo insurance market in Singapore. A brief description of the history, functions of insurance and the fundamentals of marine insurance will be given. The role of marine cargo insurance in international trade and the major players will also be touched on.